Competency Development Strategy for MSME actors in the use of ICTs in rural and urban areas in an effort to support business sustainability (Case study of MSMEs in the regency and city of Bandung) - Yanti, Vera; Sofyanty, Devy; Ong, Danny (AGUSPATI Research Institute, 2021)
This research aims (1) to analyze business competency level in rural areas and utilizing ICT facilities in Bandung, (2) to analyze MSME business competency level using ICT in rural and urban areas, and (3) to formulate appropriate strategies in developing business competition applications in business use ICTs to support business sustainability. This research was carried out in stages. Location selection is done deliberately. This research was conducted in Bandung Regency, and Bandung City from December 2018 to May 2019. The sampling technique used non proportioned stratified random sampling. The sample of respondents was 313 based on the total population selection of 3033. The data analysis method in this research used Slovin's formula, then the total sample was 323 business donors. This research used descriptive quantitative approach, inferential analysis with the Kruscall Wallis test, and the Dunn test. Based on the results of individual or part of the business competent in using ICT tools show that The SMEs of Bandung Regency are lower than the City of Bandung. The results of the overall differences of the variables that brought together MSMEs in the urban and rural areas of Bandung showed a difference. Competency development strategies that began with the first time, namely (1) Strengthening pilot business efforts using ICT facilities in the second stage (2) increasing ICT support facilities, efforts must be made through empowerment support programs, increasing motivation to increase community participation, improving training models to use ICTs that are tailored to business needs, enhance business partnerships with higher education institutions.